2012
DOI: 10.7162/s1809-48722012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Expectation as a factor of influence on the success of use of hearing aids in elderly individuals

Abstract: Introduction: Auditory prosthesis is distinguished in function of the lesser technologies that become them each time, more powerful and efficient. The marketing can generate unreal expectations how much to the results with the amplification use, mainly in inexperienced individuals. Objective: To verify the relation between expectations and success of the process of election and adaptation of auditory prosthesis in aged. Method: Clinical and experimental study, 16 aged, inexperienced individuals with the amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They also reported that satisfaction was not related to the variables gender, age, degree of hearing loss and profile electroacustic 11 . In Brazilian literature there are several studies on the satisfaction of hearing aid users who are accompanied in public services, but little is read on patients treated in private services, such as the auditives centers 5,11,12 . US researchers conducted a study comparing hearing aid users attending a private service and users of public services.…”
mentioning
confidence: 99%
“…They also reported that satisfaction was not related to the variables gender, age, degree of hearing loss and profile electroacustic 11 . In Brazilian literature there are several studies on the satisfaction of hearing aid users who are accompanied in public services, but little is read on patients treated in private services, such as the auditives centers 5,11,12 . US researchers conducted a study comparing hearing aid users attending a private service and users of public services.…”
mentioning
confidence: 99%